Temporal Branch Ablation for the Treatment of Facial Rhytids: A New Surgical Technique - Viterbo, Fausto [UNESP]; Fonseca, Eduardo; Magnani, Lucas [UNESP]; Neto, Balduino F. M. [UNESP] (Oxford Univ Press Inc, 2022)
Background: Frontal wrinkles are a cause of distress for many people as they age. Traditionally, these have been treated with botulinum toxin injections. However, this procedure is not free from complications and has a temporary result. This report describes a procedure involving temporal branch of facial nerve ablation, a novel and simple technique for the treatment and prevention of rhytids. Objectives: The objective of this study was to introduce this new technique of ablation for the treatment of frontal wrinkles after analyzing 3 options of approach based on the number of ablation lines. Methods: Fifty-one patients with a mean age of 49 years underwent nerve ablation. The temporal nerve branches were located through electrostimulation. Through a skin puncture in the temporal region, an Abbocath, with part of the plastic coating removed at its base, was introduced. The nerve branches were cauterized in oblique lines with a monopolar electric scalpel. Patients were divided into 3 groups, depending on the number of ablation lines. Results: The median follow-up period was 20 months (range, 1-50 months). Only 3 (5.7%) patients developed unilateral relapse of muscle activity in the frontal region. Group 6 was statistically superior to Group 1. There was no statistically significant difference between Group 4 and the other 2 groups. More than 70% of patients were satisfied or very satisfied with the results. Conclusions: Facial nerve branch ablation is a simple surgical technique for the treatment of forehead rhytids that produces less postoperative pain, features rapid recovery, and, above all, offers long-lasting results.